2017
DOI: 10.1002/chem.201705449
|View full text |Cite
|
Sign up to set email alerts
|

Pd‐Catalyzed β‐C(sp3)−H Arylation of Propionic Acid and Related Aliphatic Acids

Abstract: A generally applicable Pd-catalyzed protocol for the β-C(sp )-H arylation of propionic acid and related α-branched aliphatic acids is reported. Enabled by the use of N-acetyl-β-alanine as ligand our protocol delivers a broad range of arylation products. Notably, the highly challenging substrate, propionic acid, which lacks any acceleration through the Thorpe-Ingold effect, can be employed as substrate with synthetically useful yields. Furthermore, the scalability and synthetic applicability of the protocol are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 33 publications
0
30
0
4
Order By: Relevance
“…An improvement regarding the generality of the method of Zhoa has been achieved with the use of another MPAA as ligand and by using a different base and Ag salt ( Scheme 17C ). 171 This protocol showed a broad substrate scope regarding the propionic acid derivatives and also tolerated a quaternary centre at the α position to the acid. In contrast to the above method, the acid derivatives were used as limiting substrate here.…”
Section: Carboxylic Acids As Dgmentioning
confidence: 94%
See 1 more Smart Citation
“…An improvement regarding the generality of the method of Zhoa has been achieved with the use of another MPAA as ligand and by using a different base and Ag salt ( Scheme 17C ). 171 This protocol showed a broad substrate scope regarding the propionic acid derivatives and also tolerated a quaternary centre at the α position to the acid. In contrast to the above method, the acid derivatives were used as limiting substrate here.…”
Section: Carboxylic Acids As Dgmentioning
confidence: 94%
“…Advances have been made in the β-C(sp 3 )–H activation and arylation of propionic (also α-amino) acids. Zhao, 169 Yu 170 and van Gemmeren 171 all reported Pd catalysed protocols for this transformation ( Scheme 17A–C ).…”
Section: Carboxylic Acids As Dgmentioning
confidence: 99%
“…Structural variants of the anthranilic acid motif L8 and L9 gave no further improvements. Finally, a re‐investigation of amino acid derived ligands L11 – L14 showed that N ‐Ac‐β‐alanine L14 gave equally good results as L10 . Notably, this ligand performed substantially worse than L10 in an initial comparison under nonoptimized conditions.…”
Section: Methodsmentioning
confidence: 99%
“…When we examined the reactivity of substrates without a quaternary center at the β‐position, no conversion of the starting material was observed, presumably due to the absence of an accelerating Thorpe–Ingold effect. Furthermore, it should be noted that in the case of competition between β‐ and γ‐methyl groups, the β‐position is expected to react preferentially …”
Section: Methodsmentioning
confidence: 99%
“…The van Gemmeren group develops novel catalysts and concepts for the activation of challenging C−H bonds, which do not rely on the use of directing groups. Their Communication about dual ligand‐enabled nondirected C−H olefination of arenes was featured on the inside cover of Angewandte Chemie , and a Communication on palladium‐catalyzed β‐C−H arylation of aliphatic acids was published in Chemistry—A European Journal …”
Section: Awarded …mentioning
confidence: 99%